Applied SAP BI 7.0 web reports [ using BEx web analyzer and Web application designer - Jones, Peter , 1953 October 9- (McGraw-Hill, 2010)
"Distribute integrated, accurate, and timely data across your enterprise using the Web-based reporting components in SAP BI. Written by an SAP insider, Applied SAP BI 7.0 Web Reports: Using BEx Web Analyzer and Web Application Designer shows you how to construct effective queries, create HTML-based reports, and combine key analytics into a dashboard-style interface. Learn how to import data frommultiple providers, configure custom templates, track Key Performance Indicators (KPIs), and incorporate JavaScript and XHTML. Security, troubleshooting, and third-party tools are also discussed in this comprehensive guide"--Resource description p